Meeting the Needs of Evolving and Growing Elder Population: A Framework for Life-Long Learning and Program Development - Rasmusson, Xeno; Rodriguez, Lydia (Advances in Social Sciences Research Journal, 2019)
Background: The growing population of older adults will require specialized, adaptable and scalable services in order to maintain a quality of life. We offer an intergenerational and lifelong long learning model and provide guidelines for developing senior programming with relevance, accessibility and sustainability. Purpose: The aim of this work is to provide a framework for expanding and/or studying senior services. We also report on a preliminary needs assessment survey of older adults for the senior centers in their community. Method: A needs assessment questionnaire was developed and distributed to 56 men and women aged 50+ attending senior and/or community activities. Results: The vast majority (82%) were satisfied with the activities and services offered by their local senior or community center and most (74%) reported the cost was acceptable. Requested new activities included all-ages events, ukulele, scrap-booking, arts, and book clubs. Discussion: Centers looking to improve or increase senior programs should assess their local elders interests and needs. Delivering more varied activities to seniors could lead to numerous benefits, however, a number of real-world obstacles limit expanding senior services without increased cost. We recommend “senior centers” consider adding peer-mentors, and branching out to other ages, especially college students who have relevent skills and may need to volunteer for coursework or to explore career options.